2009
DOI: 10.1021/jf802262c
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Plant DNA Sequences in the Blood of Dairy Cows Fed with Genetically Modified (Bt176) and Conventional Corn Silage

Abstract: To determine whether plant sequences, including transgenic sequences, are present in animal blood, we tested blood samples from Holstein cows fed with either Bt176 genetically modified corn or conventional corn. We used previously described sensitive real-time PCR assays targeting transgenic sequences (35S promoter and Bt176 specific junction sequence), a monocopy maize-specific sequence (ADH promoter), and two multicopy sequences from plant nucleus (26S rRNA gene) and chloroplast (psaB gene). The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…On the other side, a rapid degradation throughout the gastrointestinal tract takes place (Phipps et al, 2003;Wiedemann et al, 2006), which might explain the absence of recombinant DNA in blood after feed intake. The low number of copies of cry1Ab which might cross the intestinal barrier into the blood stream would also impede the tracing of a possible transfer of recombinant DNA into the blood stream (Bertheau et al, 2009). In contrary to Bertheau et al, end-point PCR was used in this study to detect plant DNA, which might explain the absence of small fragments of rubisco in blood samples.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the other side, a rapid degradation throughout the gastrointestinal tract takes place (Phipps et al, 2003;Wiedemann et al, 2006), which might explain the absence of recombinant DNA in blood after feed intake. The low number of copies of cry1Ab which might cross the intestinal barrier into the blood stream would also impede the tracing of a possible transfer of recombinant DNA into the blood stream (Bertheau et al, 2009). In contrary to Bertheau et al, end-point PCR was used in this study to detect plant DNA, which might explain the absence of small fragments of rubisco in blood samples.…”
Section: Discussionmentioning
confidence: 89%
“…In feces, blood and urine, a 206 bp fragment of cry1Ab could not be detected by means of PCR, which is in accordance to other studies (Einspanier et al, 2001;Phipps et al, 2003;Nemeth et al, 2004). On the one side, it is reported, that genomic DNA fragments are able to cross the intestinal barrier into the blood stream (Alexander et al, 2007;Bertheau et al, 2009). On the other side, a rapid degradation throughout the gastrointestinal tract takes place (Phipps et al, 2003;Wiedemann et al, 2006), which might explain the absence of recombinant DNA in blood after feed intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model studies to detect GMOs in animal products have been carried out, showing that analysis of milk, muscle, or blood cannot serve as an indicator of the use of GMOs for feeding animals (Poms et al 2003 ;Nemeth et al 2004 ;Bertheau et al 2009 ), and a few However, particle size, composition, or heat and pressure processing might induce distortions in the results of GMO quantifi cation due to their infl uence on DNA degradation (Moreano et al 2005 ;Hird et al 2006 ). Then, cell membrane lysis by enzymatic activity and/or mechanical disruption is performed, mostly in the presence of detergents (guanidinium isothiocyanate, SDS, CTAB) and chelating agents (EDTA); cleanup steps come next, using organic solvents (chloroform, phenol); and fi nally, DNA is separated and concentrated by alcohol/salt precipitation (ethanol or isopropanol), affi nity, or ion/ exchange purifi cation columns (Hernandez et al 2005 ).…”
Section: Dna -Based Methodologies For Gmo Analysismentioning
confidence: 99%
“…Although DNA fragments from high copy number endogenous plant genes such as rubsico have been detected in the blood and digesta [11,12], transgenic DNA (tDNA) has been shown to be broken down in the rumen and duodenum of cattle [9], and a number of studies have shown that tDNA was not detected in the milk of cows fed diets containing GM feeds [11,[13][14][15][16][17][18][19]. These data from milking trials are consistent with those from wide ranging reviews of animal production trials that have focused on meat producing animals [2,20] with the conclusion that there are no detectable or reliably quantifiable traces of GM feed components in eggs, meat, or milk [2,20].…”
Section: Detection Of Transgenes In Forages and Related Agricultural mentioning
confidence: 99%